1982
DOI: 10.1063/1.331545
|View full text |Cite
|
Sign up to set email alerts
|

Minority-carrier diffusion lengths in amorphous silicon-based alloys

Abstract: In this paper, we present results of collection efficiency versus wavelength measurements on thick (⩾1 μm) amorphous silicon Schottky barrier photovoltaic devices illuminated through both the ohmic and Schottky contacts. These results enable us to infer the zero-field minority carrier diffusion length in amorphous silicon-based alloys by using an appropriate theoretical model. For intrinsic a-Si:H (hydrogen) films produced by the glow discharge of silane this was found to be ∼2,100 Å. Our novel approach of ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The purpose of the latter was to shrink w to the range where L ) w is valid [465,469,471]. Except in the very ®rst SPV-based L measurement of a-Si:H [464], L app was indeed found to decrease with increasing photo-bias, as shown in Fig.…”
Section: Limitations and Solutionsmentioning
confidence: 82%
See 2 more Smart Citations
“…The purpose of the latter was to shrink w to the range where L ) w is valid [465,469,471]. Except in the very ®rst SPV-based L measurement of a-Si:H [464], L app was indeed found to decrease with increasing photo-bias, as shown in Fig.…”
Section: Limitations and Solutionsmentioning
confidence: 82%
“…(2.61) is not the incident photon ux, but is rather the latter multiplied by the surface optical transmission and the sample quantum ef®ciency. While most authors have found re¯ectivity variations to have a negligible effect on the results in the narrow wavelength range usually probed, some have noted an in¯uence of re¯ectivity on the results [446,469], especially for low values of L [527].…”
Section: Limitations and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is another reason to develop thin film solar cells beyond the cost, it is the absorption efficiency. Since the minority carrier diffusion length is less than or around 300 nm for amorphous silicon [1-3], it is possible to improve the absorption efficiency for a thin film solar cell. Hydrogenated alloy of amorphous silicon (a-Si:H) has higher absorption coefficient than that of the crystalline silicon.…”
Section: Introductionmentioning
confidence: 99%
“…We present our analysis with crystalline silicon active region as it is the mostly used solar cell material at this time. Additionally, crystalline silicon has a carrier diffusion length of ∼100 µm, which is much greater than the ∼100 nm carrier diffusion length of amorphous (a-Si) or nanocrystalline silicon [24,25]. Therefore, all the carriers generated in a crystalline silicon active layer of sub-wavelength dimension can be fairly approximated to be collected at the contact terminals, so that a detailed light absorption calculation gives an accurate understanding of the short-circuit current density.…”
Section: Proposed Structurementioning
confidence: 99%